2018
DOI: 10.1007/s13659-018-0165-y
|View full text |Cite
|
Sign up to set email alerts
|

Compounds from African Medicinal Plants with Activities Against Selected Parasitic Diseases: Schistosomiasis, Trypanosomiasis and Leishmaniasis

Abstract: Parasitic diseases continue to represent a threat on a global scale, particularly among the poorest countries in the world. This is particularly because of the absence of vaccines, and in some cases, resistance against available drugs, currently being used for their treatment. In this review emphasis is laid on natural products and scaffolds from African medicinal plants (AMPs) for lead drug discovery and possible further development of drugs for the treatment of parasitic diseases. In the discussion, emphasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 150 publications
0
32
0
Order By: Relevance
“…Since the first bioactive isoquinoline alkaloid, morphine, was isolated from the opium plant in the early 19th century, 3 this compound class has attracted considerable scientific attention. Increasing numbers of isoquinoline alkaloids have been isolated and identified from natural sources, and various studies have reported their antitumor, antimalarial, antibacterial, antifungal, antiparasitic and insecticidal, antiviral, anti‐inflammatory, antiplatelet, and other activities 4–12 13 as reflected by several revolutionary drugs, such as the analgesic morphine, the antibacterial berberine, the antitussive codeine, 14 the antirheumatic sinomenine, 15 and the acetylcholinesterase inhibitor galanthamine 16 (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Since the first bioactive isoquinoline alkaloid, morphine, was isolated from the opium plant in the early 19th century, 3 this compound class has attracted considerable scientific attention. Increasing numbers of isoquinoline alkaloids have been isolated and identified from natural sources, and various studies have reported their antitumor, antimalarial, antibacterial, antifungal, antiparasitic and insecticidal, antiviral, anti‐inflammatory, antiplatelet, and other activities 4–12 13 as reflected by several revolutionary drugs, such as the analgesic morphine, the antibacterial berberine, the antitussive codeine, 14 the antirheumatic sinomenine, 15 and the acetylcholinesterase inhibitor galanthamine 16 (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, several plants from the Asteraceae family have provided some lead compounds against Leishmania spp. [5,6]. Specifically, Tagetes lucida Cav.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in many countries, the control of schistosomiasis is not integral of the national budget, meaning that resources are limited to overcome the morbidity and mortality associated with the disease [41,42,47]. Given the limitation in available resources and the fact that there is no available vaccine for this disease, there is a dire need to develop alternative medicines that are both cost-effective and treatment-effective for this disease [48,49]. In this advent, natural products present an interesting opportunity toward the development of novel pharmacological agents to triumph over this disease.…”
Section: Biological Control Of Intermediate Hosts As An Alternative Waymentioning
confidence: 99%